Genetic architectures of proximal and distal colorectal cancer are partly distinct - Huyghe, Jeroen R; Harrison, Tabitha A; Bien, Stephanie A; Hampel, Heather; Figueiredo, Jane C; Schmit, Stephanie L; Conti, David V; Chen, Sai; Qu, Conghui; Lin, Yi; Barfield, Richard; Baron, John A; et al. (Gut, 2021)
OBJECTIVE: An understanding of the etiologic heterogeneity of colorectal cancer (CRC) is critical for improving precision prevention, including individualized screening recommendations and the discovery of novel drug targets and repurposable drug candidates for chemoprevention. Known differences in molecular characteristics and environmental risk factors among tumors arising in different locations of the colorectum suggest partly distinct mechanisms of carcinogenesis. The extent to which the contribution of inherited genetic risk factors for CRC differs by anatomical subsite of the primary tumor has not been examined. DESIGN: To identify new anatomical subsite-specific risk loci, we performed genome-wide association study (GWAS) meta-analyses including data of 48 214 CRC cases and 64 159 controls of European ancestry. We characterised effect heterogeneity at CRC risk loci using multinomial modelling. RESULTS: We identified 13 loci that reached genome-wide significance (p<5×10-8) and that were not reported by previous GWASs for overall CRC risk. Multiple lines of evidence support candidate genes at several of these loci. We detected substantial heterogeneity between anatomical subsites. Just over half (61) of 109 known and new risk variants showed no evidence for heterogeneity. In contrast, 22 variants showed association with distal CRC (including rectal cancer), but no evidence for association or an attenuated association with proximal CRC. For two loci, there was strong evidence for effects confined to proximal colon cancer. CONCLUSION: Genetic architectures of proximal and distal CRC are partly distinct. Studies of risk factors and mechanisms of carcinogenesis, and precision prevention strategies should take into consideration the anatomical subsite of the tumour.
Keywords: alely; celogenomová asociační studie; kolon; Polymorphism, Single Nucleotide; Humans; Case-Control Studies; colon transversum; nádory tračníku; lidé středního věku; běloši; studie případů a kontrol; cancer genetics; genetická heterogenita; colon descendens; Colonic Neoplasms; jednonukleotidový polymorfismus; colon ascendens; rizikové faktory; mladý dospělý; dospělí; Aged; Colon, Descending; Colon, Transverse; Cecum; Alleles; Female; White People; senioři; cékum; lidé; Colon; Genotype; nádory rekta; věkové rozložení; Adult; Genetic Heterogeneity; colorectal cancer; ženské pohlaví; Rectal Neoplasms; Male; Middle Aged; Aged, 80 and over; cancer susceptibility; Age Distribution; Genome-Wide Association Study; Young Adult; senioři nad 80 let; genotyp; genetic polymorphisms; colon carcinogenesis; věk při počátku nemoci; mužské pohlaví; Colon, Ascending; Age of Onset; Colon, Sigmoid; colon sigmoideum; Risk Factors